1998
DOI: 10.1002/jlb.63.3.395
|View full text |Cite
|
Sign up to set email alerts
|

Effect of proteasome inhibitors on monocytic IκB-α and -β depletion, NF-κB activation, and cytokine production

Abstract: Abstract:We investigated the effect of proteasome inhibitors on the lipopolysaccharide (LPS)-induced expression of several monocytic cytokines, which may be dependent on the transcription factor, nuclear factor-B (NF-B). Exposure of human monocytic THP-1 cells to ALLN and Mu873 prevented the LPS-induced degradation of I B-␣ and -␤, as did the more potent proteasome inhibitor, PSI, whereas several calpain inhibitors were ineffective. This was accompanied by the inhibition of nuclear NF-B binding activity and NF… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
35
0
3

Year Published

1999
1999
2008
2008

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 60 publications
(42 citation statements)
references
References 54 publications
4
35
0
3
Order By: Relevance
“…Nuclear translocation of NF-B is dependent on the degradation by proteasome of its inhibitor, IB (46), and we have observed that AFAs induce NF-B nuclear accumulation. Thus, in agreement with the literature, our data are consistent with the requirement of the role of NF-B in CXCL8 and CCL2 gene transcription (47). In addition, since JNK inhibition resulted in the selective abrogation of CCL2 production, our data indicate that in dermal fibroblasts, CCL2 production also requires the transcription factor activator protein 1 (AP-1).…”
Section: Discussionsupporting
confidence: 93%
“…Nuclear translocation of NF-B is dependent on the degradation by proteasome of its inhibitor, IB (46), and we have observed that AFAs induce NF-B nuclear accumulation. Thus, in agreement with the literature, our data are consistent with the requirement of the role of NF-B in CXCL8 and CCL2 gene transcription (47). In addition, since JNK inhibition resulted in the selective abrogation of CCL2 production, our data indicate that in dermal fibroblasts, CCL2 production also requires the transcription factor activator protein 1 (AP-1).…”
Section: Discussionsupporting
confidence: 93%
“…Polyacrylamide Gel Electrophoresis and Western Blot Analysis-Cytosolic extracts were isolated as described earlier (42). Electrophoresis was performed with 12.5% polyacrylamide gels (0.1% SDS) as described previously (40).…”
Section: Methodsmentioning
confidence: 99%
“…Transfection of THP-1 Cells-The following reporter plasmids were utilized in transfection studies: 3xB.luci, a firefly luciferase reporter plasmid containing three copies of a prototypic (5Ј-GGGACTTTCC-3Ј) B site (42); TNFkop.luci, comprising 1108 base pairs of the TNF promoter region (42); and pGL2-IL-8, containing 420 base pairs of the IL-8 promoter region (44). Overexpression plasmids used in our studies included IKK-␣, IKK-␤, NIK (wild type and mutated forms), IKAP (all gifts from Tularik Inc., South San Francisco, CA), NEMO, IB-⑀ (wild type and mutated), IB-␤ (gifts from Prof. Alain Israël and co-workers, Institut Pasteur), and antisense IKK-␣ (a gift from Prof. Michael Karin, University of California-San Diego, La Jolla, CA).…”
Section: Methodsmentioning
confidence: 99%
“…min with constant shaking. Luc and ␤-gal activities were measured as described (57), and data were presented as a ratio of Luc relative light units divided by ␤-gal relative light units, according to Haas et al (58).…”
Section: Tissue Culturementioning
confidence: 99%